Being, belonging, and borders: Scandinavian creation theology as political theology. Issue 1 (18th February 2021) - Gerle, Elisabeth
Abstract: Desire for life and protecting lives has come to the fore during the pandemic. Borders have been closed to stop the spread of Covid‐19. The virus does not respect borders, yet physical distance is crucial. Three things have become clear. One is the level of uncertainty about which measures are most efficient. The other is that the neo‐liberal philosophy with "just in time" deliveries on a global market has made everyone vulnerable and invited national protectionism rather than collaboration. A third insight is that the lack of borders between wild and tame animals and human beings is connected to the emergence of the virus itself, where rain forests are exploited for short sighted profit. In the midst of this, a cry for Being, for Life, and Human Flourishing, can be heard as an underlying drumbeat. In relation to this I ponder Being in relation to Belonging and to Borders. I first describe a political landscape where neo‐nationalist, and neo‐atheist, claims for belonging, have emerged all over the world, and hence emphasized strong borders between different people, but not for capital. Secondly, I draw on resources from Scandinavian Creation Theology, especially Grundtvig, Aulén, and Wingren to paint a planetary vision with porous borders, beyond patriarchy, populism, and protectionism. In the long run there is no opting out of the planetary vulnerability. I launch the term e schatological creation theology for a creation theology that allows creation to be inspired by the Kin‐dom to come with righteousness and life in abundance.